2018
DOI: 10.18203/2394-6040.ijcmph20180218
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with female sexual dysfunction among married women in Upper Egypt; a cross sectional study

Abstract: Background: Female sexual dysfunction (FSD) has many psychological and social negative consequences. The aim of this study is to detect the potential risk factors associated with FSD among sexually active women in Beni-Suef, Egypt. Methods: A multi-stage random sampling methodology was used to include 490 premenopausal women, residing in Beni-Suef, in this cross-sectional study. FSD was measured using the Arabic version of the female sexual function index (ArFSFI), throughout an interview. It includes 6 domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
(31 reference statements)
6
9
1
1
Order By: Relevance
“…This may be attributed to, in conservative communities, such as that of Upper Egypt, speaking out about sexual problems is shameful and considered а taboo and people may get stigmatized for their sexual problems, which may hinder forming an overwhelming view over sexual issues, especially in females. 34 This is supported by the findings of the Scаndinavian study. It reported that out of 3017 women aged 20 to 60 years attending a cervical screening program, only 9.3% reported dyspareunia: 13.0% of women aged 20-29 years; 6.5% aged 50-60 years.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This may be attributed to, in conservative communities, such as that of Upper Egypt, speaking out about sexual problems is shameful and considered а taboo and people may get stigmatized for their sexual problems, which may hinder forming an overwhelming view over sexual issues, especially in females. 34 This is supported by the findings of the Scаndinavian study. It reported that out of 3017 women aged 20 to 60 years attending a cervical screening program, only 9.3% reported dyspareunia: 13.0% of women aged 20-29 years; 6.5% aged 50-60 years.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, more years of marriage carry extra burdensome tasks that interfere with sexual functioning. 34 Additionally, our results showed that 49.5% of women had inadequate family income, 68.7% of women reported morbid dyspareunia. Α longer duration of marriage may carry more stressful duties, more economic challenges, less passion for sex.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Sexual dysfunction in women is a public health issue with many physical and psychological outcomes, that affects women's quality of life 1 . Sexuality is a complex process related to neurological, vascular and endocrine systems.…”
Section: Introductionmentioning
confidence: 99%
“…10 The significant association of FSD and older age among different ethnic groups, which is maintained in the regression model, is supported by several previous studies. [11][12][13] Resumo Objetivo A incidência de obesidade, que é uma condição crônica, aumentou nos últimos anos. A associação entre obesidade e disfunção sexual feminina ainda não está clara, particularmente em mulheres após a menopausa.…”
Section: Introductionunclassified